Stray dog bite menace: an open invitation to rabies in Shimla city, Himachal Pradesh, India - Dhiman, Arvind Kumar; Mazta, Salig Ram; Thakur, Anita (International Journal Of Community Medicine And Public Health, 2017)
Shimla is the capital city of Himachal Pradesh. Shimla acts as a hub for India’s tourism sector. It is among the top 10 preferred entrepreneurial locations in India.1 City is grappling with the problem of stray dog menace. Stray dogs have established their habitats around the restaurants, hotels, hostels, hospitals and clubs here. There are around 3500-4000 stray dogs in Shimla City. In localities like the Mall Road, the Ridge, Jakhu and Summer Hill etc. the free roaming dogs are seen barking on the people.